Analisis Keamanan Data pada Sistem Informasi Berbasis Cloud Computing - Rahayu, Novi; Sumarni, Ade Titin (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Data security is crucial in the digital era, where cloud computing has become the primary solution for organizations to efficiently store and process data. However, the increasing use of cloud computing also poses significant risks related to data security and privacy. The purpose of this study is to identify challenges and solutions in maintaining data security in cloud computing systems. The method used is a systematic literature review and comparative analysis of various trusted academic sources. The results reveal key threats such as misconfigurations, unauthorized access, and data leaks, which are exacerbated by weak identity management. The study also evaluates mitigation mechanisms such as end-to-end encryption, multi-factor authentication, and a shared responsibility model between cloud service providers and users. These findings can guide the design of effective and adaptive security strategies and policies to support a secure and sustainable digital transformation. Keyword: data security; information systems; cloud computing; encryption; authentication.